Раннескифские удила на юге Восточной Европы - Махортых, С. В. (Давнина. Харківський історико-археологічний щорічник)
Резюме Махортих С. В. Ранньоскіфськи вудила на півдні Східної Європи Cтаття присвячена просторово-хронологічному аналізу та інтерпретації ранньоскифськіх металевих вудил, знайдених на Північному Кавказі і в лісостеповій Україні, які є основними центрами зосередження скіфських старожитностей VII—VI ст. до н. е. Головним типом вудил периода скіфської архаїки у Передкавказзі є бронзови та залізні вудила со стременоподібніми зовнішніми кінцями, тоді як на території Дніпровського лісостепу — залізні петельчасті вудила. Перши з них, відрізняясь типологічними характеристиками, а також різніми варіаціями декора стрижней, найбільш широке розповсюдження дістали у VII — на початку VI ст. до н. є., а други — наприкінці VII і/або VI ст. до н. е. Ключові слова: ранні скіфи, лісостепова Україна, Північний Кавказ, вудила. Summary S. Makhortykh. Early Scythian bits in the South of Eastern Europe This article is devoted to the spatial-chronological analysis and interpretation of the early Scythian horse bits, which were found in the Northern Caucasus and the foreststeppe Ukraine. These areas were the main centers of concentration of Scythian antiquities in the VII—VI centuries BC. The bronze and iron bits with stirrup-shaped loops on the both ends belong to the basic type of these bridle components in the Ciscaucasian region, whereas the iron bits with open-ended loops were the most widespread on the territory of Dnieper forest-steppe area. The former type of bits, which included finds with varied typological characteristics and variations of rods decorations, was the most widely used in VII — the beginning of VI centuries BC, while the latter type — in the end of VII and/or VI centuries BC. Key words: early Scythians, forest-steppe Ukraine, Northern Caucasus, bits.